Religious Language after J. L. Austin1 - Smith, James M. (Religious studies, 1972)
John L. Austin believed that in the illocution he had discovered a fundamental element of our speech, the understanding of which would disclose the significance of all kinds of linguistic action: not only proposing marriage and finding guilt, but also stating, reporting, conjecturing, and all the rest of the things men can do linguistically.2 We claim that the illocution, the full-fledged speech-act, is central to religious utterances as well, and that it provides a perspicuity in understanding them not elsewhere provided in the work of recent philosophy of religion. In particular we hold that understanding religious talk through the illocution shows the way in which the representative and affective elements are connected to one another and to the utterance as a whole. There may, further, be features in such an analysis which can be extended to other forms of discourse than religious.